Results of the study to propose the amount of the increase to the Minimum Wage for 2021 and its repercussions - Jiménez-Bandala, Carlos Alberto; Arellano Aceves, Diana; Márquez Olvera, Ian; Andrade Rosas, Luis Antonio; Guadarrama, Alma; Peralta, José Daniel; Sánchez, Enrique; Matus, Edgar Manuel (Revista Internacional de Salarios Dignos, 2020)
In 2019 and 2020, the increases to the Minimum Wage had a positive impact on the fall in Labor Poverty and reduced the wage gap that had existed since 1976; In this sense, this work aims to carry out a projection of a proposal to increase the minimum wage for 2021 in Mexico without affecting the variables inflation and employment. Using a data panel and a multivariate regression model, it is shown that the increase could be in a nominal range of 19 to 23% to reach an amount of between 146.63 to 151.56, in addition to showing that the salary increases had positive repercussions in the face of the CoViD-19 pandemic.